Strategi Pengembangan Objek Wisata Noyo Gimbal View melalui Community Based Tourism (CBT) - Meytria Anggita; Muhammad Miftahul Huda; Ida Swasanti (LPPM Institut Pendidikan Nusantara Global, 2026)
The development of Noyo Gimbal View tourist attraction still faces challenges related to uneven community involvement, suboptimal utilization of village potential, and unstructured management, resulting in its impact not being fully felt by residents. This study aims to formulate a tourism development strategy through a Community Based Tourism approach by examining the economic, social, cultural, environmental, and political aspects that influence destination management. The research uses qualitative methods through in-depth interviews, field observations, and documentation to understand the role of the community and stakeholders in tourism development. The results show that Noyo Gimbal View is able to encourage village economic growth through increased visits, the opening of job opportunities, and the development of local businesses. Socially, the community provides high support and is actively involved in tourism operations. Culturally, this destination plays a role in preserving local arts and traditions, while environmentally, waste management and visitor education have been implemented, although improvements are still needed. The support of the village government and the role of local economic institutions have contributed to the smooth management of the destination, but the absence of formal regulations remains an obstacle. In general, tourism development has moved towards a community-based model, but it requires strengthening community capacity, management innovation, and the formulation of more comprehensive regulations.